The type and extent of travel for professional footballers undertaking national team duties for a national football federation - Clements, E.; Ehrmann, F.; Clark, A.; Jones, M.; Lu, D.; Duffield, R. (Biology of Sport, 2023)
Elite football (soccer) involves club, continental and international fixtures, requiring players to undertake extensive travel [1]. For a national football federation, this includes the transport of players between club and camp/tournament commitments, which is often a point of contention between respective organisations [2]. Partly this contention results from the effects of travel, whereby jet lag and travel fatigue can negatively affect physical performance [3-5] and athlete wellbeing [6, 7]. Given the scarcity of data on elite players following travel, an initial step for any national football federation is to understand the volume and nature of travel undertaken by national team players. Such insight may better identify the schedule, timelines and needs of athletes` post travel. Better awareness of these travel needs can help maximise availability for training and minimise the impact of travel related stresses on performance or wellbeing. However, the regularity and volume of travel to national football team commitments has not previously been described. Further, travel demands are likely to vary significantly based on the location of the athlete and the national team camp. For countries outside of Europe, such as Australia, the travel demands and ensuing effects on player preparation can be substantial for both arrival into national team and on return to clubs [7]. Hence, detailed information regarding the type, frequency, and extent of travel for national team duties is important to aid in planning optimal travel schedules and interventions to assist players for international or club duty.